Characterization of fatigue crack growth by cyclic material forces. (15th February 2021) - Khodor, Jad; Özenç, Kaan; Lin, Guoyu; Kaliske, Michael
Abstract: The study at hand introduces a new approach to characterize fatigue crack growth at small strain elastoplasticity by cyclic material forces, cyclic configurational forces. In the theoretical framework, analyzing cyclic processes, the balance of cyclic energy momentum is derived using the cyclic free energy instead of the free energy. Moreover, the cyclic material forces acting on an inclusion within an elastic homogeneous body are derived using a modified version of Eshelby 's thought experiment. In the numerical context, cyclic nodal material forces are calculated using the weak form of the balance of cyclic energy momentum. Cyclic crack driving forces and cyclic global material forces are approximated using cyclic nodal material forces. The obtained cyclic global material forces are path-independent and show a linear correlation with the cyclic crack tip opening displacement. It is also able to characterize the effects of a single tensile overload. Finally, the results of the new approach are validated by comparing them to the experimental cyclic J -integral of a compact tension specimen. Highlights: New approach to characterize fatigue crack growth by cyclic material forces in small strain elastoplasticity. Derivation of cyclic material force acting on an inclusion. Cyclic material forces are applicable for kinematic and isotropic hardening. Cyclic material forces are path-independent and characterize the effect of a single tensile overload. Experimental results of cyclic J integral are in good agreement with the cyclic material forces.